2015
DOI: 10.1016/j.pscychresns.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of regional gray matter volume abnormalities in Alzheimer׳s disease and late life depression with hippocampal atrophy using VSRAD analysis: A voxel-based morphometry study

Abstract: Previous voxel-based morphometry (VBM) studies revealed that hippocampal volume loss in patients with late life depression (LLD) is associated with cognitive impairment and a higher risk for dementia. However, LLD patients can experience hippocampal atrophy without cognitive impairment. Thus, while LLD and AD can show comparable hippocampal atrophy, they may encompass different neuropathological changes. Using VBM, we therefore investigated differences in regional gray matter changes in 17 late-onset LLD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Moreover, because autonomic symptoms are more prominent than depressed mood or decreased motivation, the patients tend to be misdiagnosed as having a physical disease rather than MDD. Assessment of the existence of volume reduction in the three brain regions, ie, the hippocampus, sgACC, and SCA, by VBM using SPM8 and DARTEL, as in this study, provides clues to whether the patient may have dementia, MDD, or dementia plus MDD; that is, it is useful for the differential diagnosis of these conditions and for predicting the prognosis and responsiveness to drugs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because autonomic symptoms are more prominent than depressed mood or decreased motivation, the patients tend to be misdiagnosed as having a physical disease rather than MDD. Assessment of the existence of volume reduction in the three brain regions, ie, the hippocampus, sgACC, and SCA, by VBM using SPM8 and DARTEL, as in this study, provides clues to whether the patient may have dementia, MDD, or dementia plus MDD; that is, it is useful for the differential diagnosis of these conditions and for predicting the prognosis and responsiveness to drugs …”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the existence of volume reduction in the three brain regions, ie, the hippocampus, sgACC, and SCA, by VBM using SPM8 and DARTEL, as in this study, provides clues to whether the patient may have dementia, MDD, or dementia plus MDD; that is, it is useful for the differential diagnosis of these conditions and for predicting the prognosis and responsiveness to drugs. [33][34][35][36][37][38] We are aware that this study has several limitations. First, it was conducted with participants aged 54 to 80 years.…”
Section: Figurementioning
confidence: 99%
“…In addition, they could not tell us at what age the influences of the AD PGRS on the entire brain structure initially manifest. The current study used a hypothesis-free VBM analysis, which has been widely used to detect structural atrophy in individuals with AD (Shimoda et al, 2015;Whitwell et al, 2008), to estimate the effect of the AD PGRS on voxel-wise anatomical differences by exploring the whole brain. Using this data-driven approach, we showed that the AD PGRS seems to have influenced the volume of several cortical structures that had not been reported in previous ROI studies.…”
Section: Accepted Manuscript 15mentioning
confidence: 99%
“…It should be noted that previous VBM studies indicate that there is a correlation between AD and late-life depression [16,17]. Recent VSRAD studies indicate that unlike AD, patients with late-life depression show no evidence of atrophy in the precuneus and posterior cingulate cortex [18]. These findings suggest that changes in the more posterior parts of the brain may be more likely to be observed in AD.…”
Section: Discussionmentioning
confidence: 86%